2010
DOI: 10.1590/s0034-89102010000400016
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and working conditions among nursing providers

Abstract: OBJECTIVE:To evaluate working conditions associated with health-related quality of life (HRQL) among nursing providers. METHODS:Cross-sectional study conducted in a university hospital in the city of São Paulo, Southeastern Brazil, during 2004Brazil, during -2005. The study sample comprised 696 registered nurses, nurse technicians and nurse assistants, predominantly females (87.8%), who worked day and/or night shifts. Data on sociodemographic information, working and living conditions, lifestyles, and health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 21 publications
5
31
2
11
Order By: Relevance
“…The significant association between Physical Health or Psychological domains of the WHOQOL and the ERI was similar to previous findings among hospital staff members, including nurses in other countries 10,15,21) .…”
Section: Discussionsupporting
confidence: 88%
“…The significant association between Physical Health or Psychological domains of the WHOQOL and the ERI was similar to previous findings among hospital staff members, including nurses in other countries 10,15,21) .…”
Section: Discussionsupporting
confidence: 88%
“…Em um estudo transversal, com 309 profissionais de enfermagem que trabalhavam em atividades assistenciais em um hospital de grande porte em Feira de Santa, BA, foi observado que, dentre os problemas de saúde, destacaram-se as queixas e diagnósticos de problemas mentais e posturais, que podem estar associados às característi-cas do trabalho de enfermagem: atender a pacientes, enfrentar a dor, o sofrimento a morte, excesso de trabalho, elevada responsabilidade, atividades de plantão e baixa remuneração (6). Assim, a existência nos trabalhadores da saúde de condições desencadeadoras de sofrimento, estresse e ansiedade, é uma realidade não mais contestada (8,15,(17)(18)(19)(20). No entanto, as repercussões sobre a saúde desses trabalhadores, reconhecidamente expostos a fatores estressantes e ansiogênicos, ainda são pouco conhecidas e estudadas (6).…”
Section: Resultsunclassified
“…Previous studies of health personnel using different measuring tools also reported poorer scores for pain and mental/emotional domains. [7,16,19,20] interferes with self care. Stress and presence of health problem showed inverse relation with EQ VAS score.…”
Section: Discussionmentioning
confidence: 99%